Nutrients for prevention of macular degeneration and eye-related diseases - Khoo, Hock Eng; Ng, Grrace Hui Suan; Yap, Wai Sum; Goh, Henri Ji Hang; Yim, Hip Seng (MDPI, 2019)
The risk of macular degeneration can be reduced through the consumption of antioxidant-rich foods, supplements, and nutraceutical formulas. This review focuses on the antioxidants, vitamins, and minerals that have been reported for reducing the risk of macular degeneration and other eye-related diseases. Antioxidants including anthocyanins, carotenoids, flavonoids, and vitamins have been shown to reduce the risk of eye-related diseases. Anthocyanins extracted from berries are powerful antioxidants. Cyanidin, delphinidin, malvidin, pelargonidin, peonidin, and petunidin are anthocyanin aglycones detected in berries, currants, and other colored fruits and vegetables. β-Carotene, as well as xanthophyll lutein and zeaxanthin, have been reported to reduce the risk of macular degeneration. Flavonoids from plants help in the prevention of eye-related diseases through anti-inflammatory mechanisms. A combination of these antioxidants, vitamins, and minerals possess a synergistic effect on the prevention or risk reduction of macular degeneration. Formulas have been developed as dietary supplements to cater to the high demand from consumers and patients with eye problems. Many of the formulated dietary supplements that are sold in the market have been clinically proven for their efficacy to treat eye diseases. Although the bioactivities in the supplement capsules or tablets have been scientifically established for reducing risks of several diseases, which include macular degeneration and other eye-related diseases, knowledge on the right dosage, efficacy, and bioavailability of antioxidants, vitamins, and minerals is important for consumers. The information may help them make the best decision in choosing the right dietary supplements and nutraceuticals following the evidence-based recommended dosages and reference intakes for improving general health and preventing eye-related diseases. This review covers the potential causal factors involved in eye diseases, clinically proven treatments, and controversial findings on the antioxidants in the prevention of macular degeneration. Future studies should consider multiethnic and multicenter trials for eliminating potential bias in research.